BULLYING RESEARCH TREND IN ELEMENTARY SCHOOL: BIBLIOMETRIC ANALYSIS - Ari Susetiyo; Muhamad Ahyar Rasidi (MEDIA DAN STRATEGI PEMBELAJARAN, 2024)
Researchers always find bullying interesting because it has become a global case that has not been resolved, and new things always emerge. This article uses bibliometric analysis to analyze research on bullying in primary schools. The results of data analysis show that publications about bullying experience an increasing trend every year. America is the most significant contributor to psychology and social science publications worldwide, with 216 articles published. Veenstra, R. from the University of Rijksuniversiteit Groningen is the most productive and has published 19 publications, followed by Salmivalli with 15 articles